Beckman Facilities, Porterville, California (1986)
Beckman's Porterville plant opened in 1964. Between 1974 and 1983, wastes from manufacturing printed circuit boards and electronic components were disposed of onsite. The resulting contamination lead to the Environmental Protection Agency adding the plant to the Superfund National Priority List in 1986, and Beckman embarked on a two decade cleanup effort.
Keywords: Buildings; Superfund Program (U.S.); Offices; Beckman Instruments, Inc.; Women employees